PREPARATION AND CHARACTERIZATION OF SUPPORTED IRON NANOPARTICLES FOR FISCHER-TROPSCH SYNTHESIS - Tasfy, S. H. (2009)
Iron-based catalyst is a common catalyst for the Fischer-Tropsch Synthesis (FTS). The synthesis of fuel from natural gas via the FTS process is an attractive option for monetizing natural gas. Iron nanoparticles were synthesized by incipient wetness impregnation and precipitation methods. SiO2 was used as a support for the iron nanoparticles. The effect of support, promoter and iron loading on the property of the nanocatalyst was investigated using N2 physical adsorption, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and temperature programmed reduction (TPR). H2-TPR profiles for Fe/SiO2 nanocatalyst showed two reduction stages; the first peak at 370OC and the second one at 720OC. The TPR peak positions remained the same for various iron loadings. TEM image for Fe/SiO2 prepared via the impregnation method showed a well dispersed iron nanoparticles deposited on the SiO2 support. The size of iron nanoparticles ranged from 4 to14 nm.